Induction Chemotherapy Followed by Radiotherapy Versus Induction Chemotherapy Followed by Chemoradiotherapy in Locally Advanced Squamous Cell Carcinoma of Head and Neck (KYAMC Journal, 2019)
Background: Radiotherapy and chemotherapy are practiced widely for the treatment of locally advanced squamous cell carcinoma of head and neckObjectives: To compares the effectiveness and toxicities between induction chemotherapy followed by radiotherapy alone and concurrent chemoradiotherapyMaterials and Methods: A quasi experimental study was carried out from January 2014 to December 2014. Total sixty patients with locally advanced squamous cell carcinoma of head and neck origin were included and allocated into the arm A and B alternatively. Induction chemotherapy by Cisplatin and 5-Fluorouracil was given to the patient of both arms. Injection Cisplatin was given concurrently during the whole length of radiotherapy period in Arm A while patient in Arm B received radiotherapy alone. The patients were evaluated up to 30 weeks following the completion of the treatment.Results: In this study, male to female ratio was 4:1 and mean age at diagnosis was 60 ± 5 years. Overall complete response was 90% (27/30) and 53.3% (16/30) for the Arm A and Arm B respectively at 30 weeks after completion of treatment. During induction chemotherapy only 5% (3/60) of patients suffered from Grade 3 diarrhoea in both arms. In Arm A Grade 3 and 4 mucositis was observed in 36.66% (11/30) and 3.33% (1/30) of patients respectively whereas in Arm B it was 33.33% (10/30) and 3.33% (1/30) respectively.Conclusion: Induction chemotherapy followed by concurrent chemoradiotherapy is more effective than induction chemotherapy followed by radiotherapy alone in loco-regional control of locally advanced squamous cell carcinoma ofhead and neck originKYAMC Journal Vol. 10, No.-3, October 2019, Page 128-132